Perceptions and Use of Teaching Strategies for Fundamental Movement Skills in Primary School Physical Education Programs - Danielle Salters; Sara M. Scharoun Benson (MDPI AG, 2022)
Fundamental motor/movement skills (FMS) describe the basic skills necessary to complete physical tasks, and are a key aspect of primary school physical education (PE) programs. Yet, specific teaching styles for FMS development have been relatively unexplored. Through a mixed-methods design, experiences and perceptions of different PE teachers (preservice, specialist, and generalist) were explored. The Spectrum of Teaching Styles (STS) survey was used to quantify self-reported use of teaching styles that may be used by PE teachers (N = 102). Semi-structured, qualitative interviews with a subset of participants (N = 11) were employed to explore how PE teachers perceive FMS development in PE classes. Combined, the findings highlight a preference for collaborative approaches to teaching and learning in PE, with a specific preference for explicit teaching strategies. Survey results demonstrated a preference for Style B (the practice style), which promotes teacher facilitation of activities and constructive feedback, with opportunities for students to practice skills and receive feedback. Teachers described how confidence with PE content influences the ability to provide lessons that target FMS development; this was reinforced by desires for additional professional development and training. Together, the findings provide a holistic view of teaching styles used in PE for FMS development, and outline a need to explore teaching approaches used by different PE teachers.